Clinical factors that influence the occurrence of symptomatic pseudoaneurysms and arteriovenous fistulas after partial nephrectomy: multi-institutional study of renal function outcomes after one year of selective arterial embolization - Lee,Chan Ho (2021)
ABSTRACT Purpose: Renal artery pseudoaneurysms (RAPs) and arteriovenous fistulas (AVFs) are rare but potentially life-threatening complications after partial nephrectomy (PN). Selective arterial embolization (SAE) is an effective method for controlling RAPs/AVFs. We assessed the clinical factors affecting the occurrence of RAPs/AVFs after PN and the effects of SAE on postsurgical renal function. Materials and Methods: Four hundred ninety-three patients who underwent PN were retrospectively reviewed. They were placed in either the SAE or the non-SAE group. The effects of clinical factors, including R.E.N.A.L. scores, on the occurrence of RAPs/AVFs were analyzed. The influence of SAE on the estimated glomerular filtration rate (eGFR) during the first postoperative year was evaluated. Results: Thirty-three (6.7%) patients experienced RAPs/AVFs within 8 days of the median interval between PN and SAE. The SAE group had significantly higher R.E.N.A.L. scores, higher N component scores, and higher L component scores (all, p <0.05). In the multivariate analysis, higher N component scores were associated with the occurrence of RAPs/AVFs (Odds ratio: 1.96, p=0.039). In the SAE group, the mean 3-day postembolization eGFR was significantly lower than the mean 3-day postoperative eGFR (p <0.01). This difference in the eGFRs was still present 1 year later. Conclusions: Renal tumors located near the renal sinus and collecting system were associated with a higher risk for RAPs/AVFs after PN. Although SAE was an effective method for controlling symptomatic RAPs/AVFs after PN, a procedure-related impairment of renal function after SAE could occur and still be present at the end of the first postoperative year.